Study on the Relationship Between Respiratory Distress Syndrome and SP-A1 (rs1059057) Gene Polymorphism in Mongolian Very Premature Infants - Wang, Xiaoli; Zhang, Yuheng; Mei, Hua; An, Caiyan; Liu, Chunzhi; Zhang, Yayu; Zhang, Yanbo; Xin, Chun (Frontiers in Pediatrics, 2020)
Aim: To study the relationship between rs1059057 polymorphism of pulmonary surfactant protein A1 (SP-A1) and respiratory distress syndrome (RDS) in Mongolian very premature infants. Methods: Applying the strategy of case-control study, one hundred and twenty Mongolian RDS very premature infants (58 males and 62 females) in the western part of Inner Mongolia were selected as the case group, and 120 subjects of non-RDS very premature infants (56 males and 64 females) with the same nationality, same sex and similar gestational age were used as the control group. The single nucleotide polymorphism (SNP) site rs1059057 of SP-A1 was genotyped using polymerase chain reaction-single strand conformational polymorphism (PCR-SSCP). Results: Two genotypes, A/G and A/A, were detected at the SP-A1 rs1059057 locus in the western part of Inner Mongolia. In the case group, the frequencies of two genotypes were 53% and 47%, and the frequencies of A allele and G allele were 73% and 27%, respectively. In the control group, the frequencies of the two genotypes were 42% and 58%, and the frequencies of A allele and G allele were 79% and 21%, respectively. There was no significant difference in the genotype frequency of SP-A1 (rs1059057) locus between the case group and the control group (X2 = 3.275, P＞0.05), and no significant difference in allele frequency between the case group and the control group (X2 = 2.255, P > 0.05). Conclusion: The genotypes and allele frequencies of SP-A1 (rs1059057) locus were not associated with the incidence of RDS in Mongolian very premature infants in western Inner Mongolia.